PERKAWINAN BEDA AGAMA: PERSPEKTIF ISLAM PROGRESIF - Masthuriyah Sa’dan (UIN Sayyid Ali Rahmatullah Tulungagung, 2016)
The discourse of interfaith marriage evoked controversy. Article 2 (1) of LawNo 1 in 1974 on marriage does not discus interfaith marriage. The law doesnot legalize interfaith marital. The ban on interfaith marriage is reaffirmedby MUI No 4 / MUNAS VII / MUI / 8/2005 concerning interfaith marriage. Interfaith marriage is illegitimate and forbidden on the basis set forth in the Koran and Hadith. Contrary to the Law on Marriage and the MUI fatwa, the Progressive Islamic circle argues that interfaith marriage to either non-Muslim man or women, is allowed and legitimate.Keywords: Inter-religious Marriage, Islam Progressive